EXPLORING CARTOON STORY MAKER APPLICATION AS AN INSTRUCTIONAL MEDIA IN WRITING NARRATIVE TEXT IN SENIOR HIGH SCHOOL - Neng Tari Aulianisa (Universitas Suryakancana, 2019)
This research investigated the implementation of cartoon story maker application as an instructional media in writing narrative text class, then to find out the strengths and weaknesses of cartoon story maker application as an instructional media in writing narrative text, and to find out the students’ response in writing narrative text by using cartoon story maker application as an instructional media. This study was conducted at a senior high school in Cianjur. The qualitative method was the research designed in this study. Therefore, observation, questionnaire, and interview were employed as the data collection in this research. The findings showed that cartoon story maker application creates fun learning and enjoyable learning for students and had a good atmosphere in the classroom, several strengths and weaknesses of cartoon story maker application. Besides the researcher also described their responses in writing narrative text by using cartoon story maker application. Cartoon story maker gives good impact for students, most of students give positives responses. It is supported by the fact that they enjoyed their writing process using cartoon story maker. To sum up, since the implementation of cartoon story maker has positive responses from the students and able to help them, this instructional media can be implemented in teaching writing narrative text in senior high school.